Implementasi Pendekatan Aktuaria Untuk Perhitungan Dana Pensiun - Anita Talia; Danu Rama Dani; Zahra Putri (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
A pension fund program is a crucial instrument in the social security system, playing a vital role in ensuring economic stability and financial well-being for individuals in their later years. This program is designed as a form of long-term financial planning aimed at providing protection for workers after they enter retirement. Through this, workers are promised structured benefits in the form of pension funds or allowances, ensuring sustainable income security. Long-term financial planning, particularly for retirement, has become an essential need in the modern economy. This research explores the implementation of actuarial approaches in pension fund calculations utilizing Python programming to enhance the calculation process. The research aims to determine the total promised pension funds allocated across the working period to calculate funding requirements more systematically. Simulated data is used to compare manual calculation results with Python-based estimations. Python is expected to provide additional efficiency in estimating future pension needs. The findings demonstrate that actuarial calculation methods, supported by programming technology, can enhance accuracy in projections and assist in determining the appropriate amount for pension fund programs.